Critical roles of long noncoding RNAs in breast cancer. Issue 6 (17th January 2020) - Abolghasemi, Maryam; Tehrani, Sadra S.; Yousefi, Tooba; Karimian, Ansar; Mahmoodpoor, Ata; Ghamari, Aliakbar; Jadidi‐Niaragh, Farhad; Yousefi, Mehdi; Kafil, Hossein S.; Bastami, Milad; Edalati, Mahdi; Eyvazi, Shirin; et al.
Abstract: Breast cancer is a major clinical challenge that affects a wide range of the female population and heavily burdens the health system. In the past few decades, attempts have been made to understand the etiology of breast cancer, possible environmental risk factors, and the genetic predispositions, pathogenesis, and molecular aberrations involved in the process. Studies have shown that breast cancer is a heterogeneous entity; each subtype has its specific set of aberrations in different cell signaling pathways, such as Notch, Wnt/β‐catenin, transforming growth factor‐β, and mitogen‐activated protein kinase pathways. One novel group of molecules that have been shown to be inducted in the regulation of multiple cell signaling pathways is the long noncoding RNAs (lncRNAs). These molecules have important implications in the regulation of multiple signaling pathways by interacting with various genes, affecting the transcription process, and finally, playing roles in posttranslational control of these genes. There is growing evidence that lncRNAs are involved in the process of breast cancer formation by effecting the aforementioned signaling pathways, and that this involvement can have significant diagnostic and prognostic values in clinical contexts. The present review aims to elicit the significance of lncRNAs in the regulation of cell signaling pathways, and the resulting changes in cell survival, proliferation, and invasion, which are the hallmarks of breast cancer. Abstract : The present review aims to elicit the significance of long noncoding RNAs (lncRNAs) in the regulation of cell signaling pathways, and the resulting changes in cell survival, proliferation, and invasion, which are the hallmarks of breast cancer.